Application of hos for heart rate variability - Zhemchuzhkina, T. V.; Abdallah, Iren (My University, 2022)
This work is devoted to calculation of higher order spectra (HOS) of ECG signals and comparing of results of standard spectral and statistical methods and HOS methods for heart rate variability (HRV) analysis. Heart rate variability (HRV) is a useful signal for understanding the status of the automatic nervous system.
Keywords: heart rate variability; higher order spectra; nervous system